SedInConnect: a stand-alone, free and open source tool for the assessment of sediment connectivity. (February 2018) - Crema, Stefano; Cavalli, Marco
Abstract: There is a growing call, within the scientific community, for solid theoretic frameworks and usable indices/models to assess sediment connectivity. Connectivity plays a significant role in characterizing structural properties of the landscape and, when considered in combination with forcing processes (e.g., rainfall-runoff modelling), can represent a valuable analysis for an improved landscape management. In this work, the authors present the development and application of SedInConnect: a free, open source and stand-alone application for the computation of the Index of Connectivity (IC), as expressed in Cavalli et al. (2013) with the addition of specific innovative features. The tool is intended to have a wide variety of users, both from the scientific community and from the authorities involved in the environmental planning. Thanks to its open source nature, the tool can be adapted and/or integrated according to the users' requirements. Furthermore, presenting an easy-to-use interface and being a stand-alone application, the tool can help management experts in the quantitative assessment of sediment connectivity in the context of hazard and risk assessment. An application to a sample dataset and an overview on up-to-date applications of the approach and of the tool shows the development potential of such analyses. The modelled connectivity, in fact, appears suitable not only to characterize sediment dynamics at the catchment scale but also to integrate prediction models and as a tool for helping geomorphological interpretation. Highlights: We present a tool for the computation of an Index of Connectivity. The tool is developed in Python with an easy to use interface. An overview on applications following the same approach is reported. Results allow the characterization of sediment dynamics for landscape management.